Black knowledges/Black struggles : essays in critical epistemology - Ambroise, Jason R.; Bröck-Sallah, Sabine, 1954- (FORECAAST., 2015)
"Explores the central but often critically neglected role of knowledge and epistemic formations within social movements for Black 'freedom' and emancipation. The collection examines the structural subjugation and condemnation of Black African and Afro-mixed descent peoples globally within the past 500 years of trans-Atlantic societies of Western modernity, doing so in connection to the population's dehumanization and/or invisibilization within various epistemic formations of the West."